“The More the Better” Paradox of Antenatal Ultrasound Examinations in Low-Risk Pregnancy - Chiossi, Giuseppe; Palomba, Stefano; Balduzzi, Sara; Costantine, Maged M.; Falbo, Angela I.; La Sala, Giovanni B. (American Journal of Perinatology, 2016)
Objective To investigate whether different antenatal care models could account for differences in operative delivery rates and adverse neonatal outcomes among low-risk pregnant women, and to identify independent variables associated with delivery modes and adverse neonatal outcomes.Study design Retrospective cohort from a single center of singleton, term, live births between January 2012 and June 2014. Rates of cesarean deliveries, operative vaginal deliveries, and neonatal morbidities were analyzed among women followed by private obstetrician-gynecologists versus national health system providers (certified nurse midwifes supervised by obstetrician-gynecologists), and adjusted for potential confounders.Results Among the 2,831 women in our cohort, obstetric and neonatal outcomes were independent of obstetric providers. After we controlled for confounders, private patients having more than four antenatal ultrasound examinations were more likely to undergo cesarean delivery than public patients with four or fewer sonographic assessments (five to eight prenatal scans: relative risk ratio, 3.3; 95% confidence interval [CI] 1.4–8; nine or more prenatal scans: relative risk ratio, 4.1; 95% CI 1.2–14).Conclusions Multiple prenatal ultrasound examinations in low-risk obstetric populations appear to be an independent and potentially modifiable risk factor for cesarean deliveries.
Keywords: cesarean delivery; operative delivery; prenatal ultrasound scanning; private patients